Dominating, Protecting, Creating. A Philosophical Essay about Utopianist Attitudes (Res Publica. Revista de Historia de las Ideas Políticas, 2017)
Environmental issues captures international attention in a daily base and shapes in a great extent the fantasies of contemporary society about an imminent Apocalypse. Again and again the end of the world is announced coupled with apocalyptic settings based in a Nature’s revenge for being victim of the irresponsible and devastating human progress. Our aim is to propose a utopian approach to environmental crisis to cope with the following issues: counter-instructions from classical utopias, anti-utopian claims against political alternatives, institutional solutions based on sustainability and paralyzing fears from a frightening ecologism. Also, we will try to elucidate ontological differences between Modern and Post-Modern utopia, reclaiming the need and feasibility of a new utopianism.